Choice and competition in education: an endless controversy? - Neves, Vítor (2018)
Choice and competition are two buzzwords in the current discourse on education. It is often argued that in order to achieve better education, “freedom of choice” and more competition among schools are needed. This article questions this assertion. It discusses the concepts of choice and competition and claims that, rather than a technical issue (as economists usually maintain), the desirability or otherwise of adopting market mechanisms in education is, first of all, an issue regarding the purposes of education, and how the means chosen influence the goals that individuals and society aim to attain.